PWE-177 An Audit to Evaluate the Safety and Efficacy of Percutaneous Endoscopic Gastrostomy (PEG) Placement in Patients with Learning Disabilities. (4th June 2013) - Black, C; Shaw, I; Ayres, L
Abstract : Introduction: Guidelines exist to aid clinicians in selecting patients likely to benefit from percutaneous endoscopic gastrostomy (PEG) placement. Patients with learning disabilities (LD) are distinct from those with dementia in whom PEG placement in not usually recommended 1 . We report our experiences of PEG placement in patients with learning disabilities and our use of a specially designed pathway which emphasises multi-disciplinary team (MDT) input. Methods: To describe the efficacy and safety of PEG insertion in patients with LD, we retrospectively analysed a cohort of 42 patients with severe LD who required nutritional support. We reviewed their medical case notes and their dietetic notes. Results: Forty two patients underwent 117 procedures: 38 index PEG insertions, 43 PEG replacements, 35 percutaneous endoscopic gastrojejunostomy (PEGJ) replacements and 1 PEG removal (6 procedures (5.1%) were unsuccessful). Best interest meeting or MDT assessment took place in all patients. General anaesthetic was required for 34 (29%) procedures. Mean weight pre-PEG was 39.8 Kg and mean weight after a median follow-up of 21.5 months was 46.1 Kg (mean overall weight gain = 2.3 kg). 30 day mortality was zero. Complications were common (74%) and included perforation n = 1, aspiration pneumonia n = 13, tube displacement n = 10, PEG site infection n = 4. In 2 cases of unsuccessful PEG insertion surgical feeding gastrostomy was required. On-going vomiting occurred in 6 patients (14.3%) prompting conversion to PEG-J in 5 cases. Conclusion: We found that PEG placement in LD patients was a positive intervention for the majority. Although there were frequent late complications such as aspiration pneumonia and PEG displacement, these reflect the complex underlying medical and social needs of the patients concerned. Overall, PEG placement appears to be safe and results in a modest weight gain; PEG-J should be considered for those with on-going vomiting. The use of a pathway for PEG placement ensures MDT input, appropriate patient selection, better pre-procedure planning e.g. use of general anaesthesia, and appears to promote good patient outcomes. Disclosure of Interest: None Declared. Reference: Westaby, D. et al. The provision of a percutaneously placed enteral tube feeding service. Gut 2010; 59: 1592–1605.